Prevalence and clinical correlates of misophonia symptoms in the general population of Germany - Jakubovski, Ewgeni; Müller, Astrid; Kley, Hanna; de Zwaan, Martina; Müller-Vahl, Kirsten (Frontiers in Psychiatry, 2022)
Introduction Misophonia refers to a phenomenon in which affected individuals have a selective intolerance to sounds of mostly oral or nasal origin. This intolerance is typically associated with strong emotional reactions such as anger, irritation, and disgust. The aim of this study was to conduct the first large epidemiological survey to determine the prevalence of misophonia symptoms in the adult population in Germany. Methods We conducted a large-scale representative population survey between December 2020 and March 2021. For this purpose, a sample of 2,519 people were visited in their households and assessed with the Misophonia Questionnaire (MQ) and the Amsterdam Misophonia Questionnaire (AMISOS-R) to document misophonic symptoms. The primary estimate of clinical misophonia symptoms prevalence was based on the MQ Severity Scale and a secondary estimate was based on the AMISOS-R. The survey further included self-ratings to measure perfectionism, not-just-right experience (NJRE), autonomous sensory meridian response (ASMR) and general health as well as demographic data. Results Five percent of the sample scored equal or above the MQ Severity Scale threshold for clinical misophonia symptoms (5.9% based on AMISOS-R). Individuals with clinical misophonia symptoms had a higher rate of perfectionism, a higher occurrence of NJRE, higher susceptibility to ASMR, and a worse general health status than those scoring below the cut-off-score. All those factors also independently predicted the severity of misophonia symptoms in a multiple regression model. Conclusion Misophonia is a frequent condition and should further be examined as an independent diagnostic entity.